The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsnano.9b06311
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Transparent Ultraviolet Photodetectors Based on InGaZnO Superlattice Nanowire Arrays

Abstract: Due to the efficient photocarrier separation and collection coming from their distinctive band structures, superlattice nanowires (NWs) have great potential as active materials for high-performance optoelectronic devices. In this work, InGaZnO NWs with superlattice structure and controllable stoichiometry are obtained by ambient-pressure chemical vapor deposition. Along the NW axial direction, perfect alternately stacking of InGaO(ZnO) 4 + blocks and InO 2 − layers is observed to form a periodic layered struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…As shown in Figure h,i, the I – t (current–time) curve, with the UV light of 1.25 mW cm –2 switching on and off every 10 s, the stoichiometric GaS shows very stable and consistent performance with a sharp edge, indicating instant response. The response time is less than 66 ms (Figure S6, Supporting Information), which is two to three orders less than other visible‐light blind UV photodetectors (Table S1, Supporting Information) . However, the photocurrent of GaS 0.87 decreased drastically as soon as the light was on, and continued with every switching on of the light, dropping to only half of its starting values after only a total of 110 s exposure.…”
mentioning
confidence: 93%
“…As shown in Figure h,i, the I – t (current–time) curve, with the UV light of 1.25 mW cm –2 switching on and off every 10 s, the stoichiometric GaS shows very stable and consistent performance with a sharp edge, indicating instant response. The response time is less than 66 ms (Figure S6, Supporting Information), which is two to three orders less than other visible‐light blind UV photodetectors (Table S1, Supporting Information) . However, the photocurrent of GaS 0.87 decreased drastically as soon as the light was on, and continued with every switching on of the light, dropping to only half of its starting values after only a total of 110 s exposure.…”
mentioning
confidence: 93%
“…2,5 Other noteworthy features of this system and, in particular, in the case of In 2-x Ga x O 3 (ZnO) m nanowires, are the improvement of the thermoelectric figure of merit by 2.5 orders of magnitude, in comparison to undoped ZnO nanowires, and the excellent sensitivity to ultraviolet light irradiation as photodetectors. [21][22][23] In the case of Al 3+ doping, Košir et al 24 reported the improvement of the thermoelectric properties caused by the small addition of Al 3+ in Zn 5 In 2 O 8 ceramics. On the other hand, only few studies about the influence of In 3+ substitution in the luminescent properties of IMZOs (M=Ga, Al) performed on microwires have been reported so far.…”
mentioning
confidence: 99%
“…[50] In these cases, the interaction of simultaneous light pulses with adsorbed and bulk oxygen in the surface depletion region play a key role in regulating the NW conductance, that is, the synaptic weight. [9,51] In a recent work, both volatile and non-volatile resistive switching have been achieved in Ag-contacted ZnO nanowire devices, mainly enabled by the atomic Ag diffusion along the NW (Figure 2f,g), which well emulate the ion migration dynamics in biological synapses. [35] With detailed investigation of the memristive mechanism in the Ag-ZnO system, the underlying electrochemical fundamentals of filament formation/dissolution highlight the Ag + /Ag redox reactions and transport characteristics on the crystalline NW surface.…”
Section: D Quantum Materials For Artificial Synapsesmentioning
confidence: 91%